A new injury prevention program `FUNBALL` improves cognitive performance of young football (soccer) players: A cluster randomized controlled trial - Meha, R.; Obërtinca, R.; aus der Fünten, K.; Leisge, K.; Schaefer, S. (Psychology of Sport and Exercise, 2024)
The youth football injury prevention program `FUNBALL` contains exercises requiring high cognitive demands, which are performed concurrently to the training of the respective motor task. This study evaluates whether the program increases cognitive performances of young football players.